Critical Issues in an Unmotivated Patient with Alcohol Dependence - Nidhi Vadhavekar; Saloni Chatwani; Avinash Desousa; Hardik Sheth; Kavitha V. Dongerkery; Pradnya Deolekar (Annals of Indian Psychiatry)
Alcohol use disorder (AUD) is characterized by an impaired ability to stop alcohol consumption despite its adverse sociooccupational, health consequences and is associated with tolerance and withdrawal on sudden stoppage of alcohol. The patient had a history of AUD, alcoholic liver cirrhosis, HIV, and squamous-cell carcinoma of the vocal cords. The patient’s AUD was characterized by cluster B personality disorder traits, and treatment involved a multidisciplinary approach (acamprosate, sertraline, nicotine replacement therapy, psychotherapy, and admission into a rehabilitation center). However, all interventions failed, and the patient’s medical complications ultimately led to his demise. This case highlights the importance of considering a range of factors that contribute to poor treatment response in AUD, including motivation, personality factors, and medical comorbidities. This case also highlights the fact that there is an urgent need for stricter regulation of rehabilitation facilities in India, particularly those catering to patients with complex and comorbid conditions.